The traumatic consequences of Boko Haram slavery among the ethnic minorities of southern Borno, Borno State, Nigeria - Samaila Ziradzo; Robert T. Netangaheni (AOSIS, 2022)
Background: The investigation on the experiences of Kibaku ethnic minorities of southern Borno in the Federal Republic of Nigeria under the Boko Haram (BH) insurgency is inevitable, considering the dire humanitarian situation that has since prevailed. The mass massacre indicates the violation of human rights. Aim: To explore, describe and analyse the BH insurgency in north-eastern Nigeria and its traumatic effects which may be experienced at several interrelated levels. Setting: The research was conducted within the Kibaku ethnic communities of Chibok local government areas of Southern Senatorial District in Borno State of Nigeria. Methods: A predominantly exploratory and descriptive qualitative research design approach was adopted with a total of 80 participants. Results: The health consequences of BH-inspired victimisation include sexually transmitted diseases such as AIDS and chronic infections, unwanted pregnancy, miscarriage and other reproductive health problems. The psycho-emostional effects are both incalculable and unquantifiable, which is compounded by grief for the loss of victims through either abduction or death. Conclusion: The unjustifiable mass violence against the minorities may, from a historical viewpoint, be an orchestrated suffering of humans at the hands of other 'humans' in north-eastern Nigeria. Contribution: This article will add to the body of knowledge considering the magnitude (scale) and implications (scope) of the genocidal violence meted by a motley of sectarian malcontents propagating some illogical, unscientific, and historically ideologies bothering on a combination of racial bigotry, ethnicity and religious intolerance in Nigeria.